2001
DOI: 10.1046/j.1471-4159.2001.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of 14 genes in amyotrophic lateral sclerosis spinal cord detected using gridded cDNA arrays

Abstract: In order to obtain insight into the aetiology and pathogenesis of amyotrophic lateral sclerosis (ALS), high‐density gene discovery arrays (GDA human version 1.2) containing 18 400 non‐redundant EST cDNAs pooled from different tissue libraries have been used to monitor gene expression in lumbar spinal cord from ALS cases compared with controls. Quantitative filter analysis revealed differential expression of cDNAs normalized to internal standards. These candidates have been further investigated and their expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 60 publications
3
50
0
Order By: Relevance
“…Also, three other cases (one FTD, one CBS and one normal control) showed decreased PGRN expression levels, but no variants/mutations were identified (Coppola et al 2008). Finally, as well as in a previous study on ALS cases (Malaspina et al 2001), a correlation between greater PGRN mRNA levels and disease status, in this case AD, was reported (Coppola et al 2008). Another study showed that PGRN protein was strongly reduced (3.93 times) in both the plasma and cerebrospinal fluid (CSF) of affected and unaffected individuals carrying PGRN L271LfsX10 and Q341X mutations (Ghidoni et al 2008).…”
Section: Pgrn Expression/plasma Levels: a Useful Diagnostic Tool?supporting
confidence: 75%
“…Also, three other cases (one FTD, one CBS and one normal control) showed decreased PGRN expression levels, but no variants/mutations were identified (Coppola et al 2008). Finally, as well as in a previous study on ALS cases (Malaspina et al 2001), a correlation between greater PGRN mRNA levels and disease status, in this case AD, was reported (Coppola et al 2008). Another study showed that PGRN protein was strongly reduced (3.93 times) in both the plasma and cerebrospinal fluid (CSF) of affected and unaffected individuals carrying PGRN L271LfsX10 and Q341X mutations (Ghidoni et al 2008).…”
Section: Pgrn Expression/plasma Levels: a Useful Diagnostic Tool?supporting
confidence: 75%
“…In ALS research, while there have been several transcriptomic studies of central nervous and peripheral human tissues, animal and cell models, the complete picture is still being elucidated. Large lists of differentially expressed genes have been generated (Dangond et al 2004;Jiang et al 2005;Malaspina and de Belleroche 2004;Malaspina et al 2001;Rabin et al 2010;Saris et al 2009;Wang et al 2006;Zhang et al 2011), and although there are discrepancies between individual members of gene lists, there is a high degree of overlap in the molecular pathways predicted to be involved in this complex disease (Henriques and Gonzalez De Aguilar 2011;Heath et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We found 60 genes that were differently expressed in the spinal cords of sALS patients as compared to controls. Some of the differently expressed genes, such as astrocyte glial fibrillary acidic protein (GFAP), cathepsin B, and Apo E, are know to be associated with ALS (Masliah et al 1996;Lacomblez et al 2002;Malaspina et al 2001), whereas other Ratios higher than 1 are upregulated in ALS, whereas ratios lower than 1 are downregulated in ALS. p<0.05 for all the presented genes NCBI = National Center for Biotechnology Information genes such as LYST, EGFR, and ferritin are reported here for the first time in association with ALS.…”
Section: Discussionmentioning
confidence: 99%